2018
DOI: 10.1038/s41598-018-34526-0
|View full text |Cite
|
Sign up to set email alerts
|

Collective antiskyrmion-mediated phase transition and defect-induced melting in chiral magnetic films

Abstract: Magnetic phase transitions are a manifestation of competing interactions whose behavior is critically modified by defects and becomes even more complex when topological constraints are involved. In particular, the investigation of skyrmions and skyrmion lattices offers insight into fundamental processes of topological-charge creation and annihilation upon changing the magnetic state. Nonetheless, the exact physical mechanisms behind these phase transitions remain unresolved. Here, we show numerically that it i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…This antiskyrmion also fulfils topological charge conservation, at the precise moment of skyrmion merging. The reverse mechanism is similar to one suggested for skyrmion lattice inversion during polarity switching of an applied external magnetic field, whereby antiskyrmions are formed at the point of skyrmion core merging 18 .…”
Section: Skyrmion Creation and Annihilation Mechanismssupporting
confidence: 64%
See 1 more Smart Citation
“…This antiskyrmion also fulfils topological charge conservation, at the precise moment of skyrmion merging. The reverse mechanism is similar to one suggested for skyrmion lattice inversion during polarity switching of an applied external magnetic field, whereby antiskyrmions are formed at the point of skyrmion core merging 18 .…”
Section: Skyrmion Creation and Annihilation Mechanismssupporting
confidence: 64%
“…Therefore, the results may only give approximations to the true pathway. We chose ultra-thin films at zero temperature in order for the simulations to be valid, given the thickness-temperature-field phase space of B20 FeGe 20 . Finally, the micromagnetic simulations were performed to support insight into the mechanistic pathways which are currently inaccessible experimentally due to timescales.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in realistic conditions, disordered pinning sites which generally exist in sputtered films may widen the range of critical fields for skyrmion annihilation, or may energetically favour worm-like textures [28]. In such cases the system undergoes gradual metamagnetic transitions which are reflected in a smooth variation of ρ TH xy − B ext loops [28,53,54] rather than the sharp jumps shown in Fig. 4b.…”
Section: Engineering Layer-dependent Properties For 3d Multistatesmentioning
confidence: 99%
“…Karube et al 55 have also observed antiskyrmions in a chiral magnet with S 4 symmetry. Pierobon et al 56 have shown numerically that the application of a magnetic field to a skyrmion lattice can produce an "inverted" lattice phase by producing antiskyrmions. Directly relevant to this work, Jena et al 1 and Peng 2 have observed both antiskyrmions and elliptically distorted skyrmions in the material Mn 1.4 Pt 0.9 Pd 0.1 Sn which also has the D 2d crystal symmetry.…”
Section: Introductionmentioning
confidence: 99%